Soil characteristics and microbial responses in post-mine reclamation areas in a typical resource-based city, China - Tan, Min; Zhou, Xu; Li, Gang; Ge, Mengyu; Chen, Zhuang; Qu, Junfeng (Journal of Environmental Engineering and Landscape Management, 2021)
Mining activities worldwide have resulted in soil nutrient loss, which pose risks to crop and environmental health. We investigated the effects of post-mine reclamation activities on soil physicochemical properties and microbial communities based on 16S rRNA sequencing and the further statistical analysis in the coal base in Peixian city, China. The results revealed significant differences in soil microbial relative abundance between reclamation and reference soils. Proteobacteria was the most abundant phyla in all seven mine sites regardless of reclamation age while considerable differences were found in microbial community structure at other levels among different sites. Notebly, Gammaproteobacteria, member of the phylum Proteobacteria, had relatively high abundance in most sites. Furthermore, Kendall’s tau-b correlation heatmap revealed that potentially toxic elements and other physicochemical properties play vital roles in microbial community composition.